PENGARUH SUBSTITUSI SUSU BUBUK FULL CREAMDENGAN JAMBU BIJI MERAH (Psidium guajava) TERHADAP SIFAT FISIK DAN SENSORIS ES KRIM - , NOVIANTIKA NUR S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study was based on claim of lower fat content food as healthy food. Pink fleshed guava used as substituent of full cream milk powder in ice cream formulas to produce ice cream with lower fat content. This substitution was significantly increases ice cream mix viscosity, overrun, and melting retention of ice cream, while 14,3% pink fleshed guava usage also significantly reduces hardness and sandy texture of ice cream. Best formula found as usage of 14,7% full cream milk powder, 63% whole milk, 8% cane sugar, and 14,3% pink fleshed guava which produced ice cream with 6% fat.